Sistem Peringatan Dini Bencana Banjir Berbasis Mikrokontroler ATmega16 dengan Buzzer dan Web-Based - Alfi febriawan Febriawan; Deni Suprihadi (Universitas Kebangsaan Republik Indonesia, 2025)
Flooding is one of the natural disasters that often occurs due to high rainfall and overflowing rivers. Sumbersari Village, especially in Sapan Village, often experiences flooding due to the overflowing Citarum River. Therefore, a flood detection tool is needed to provide early warning to the community in order to reduce the risk and losses due to flooding. This study aims to design and develop an Arduino Uno-based flood early warning system with a fuzzy approach. This system uses an HC-SR04 ultrasonic sensor to measure water levels and a raindrop detection sensor to detect rain intensity. Data from the sensor is processed by the Arduino Uno microcontroller and displayed via a buzzer and a web-based platform. The test results show that this tool has high accuracy in monitoring water levels and providing real-time warnings to the community around the river flow. It is hoped that this system can be an effective solution in flood disaster mitigation.